Design of synthetic extracellular matrices for probing breast cancer cell growth using robust cyctocompatible nucleophilic thiol-yne addition chemistry. (September 2018) - Macdougall, Laura J.; Wiley, Katherine L.; Kloxin, April M.; Dove, Andrew P.
Abstract: Controlled, three-dimensional (3D) cell culture systems are of growing interest for both tissue regeneration and disease, including cancer, enabling hypothesis testing about the effects of microenvironment cues on a variety of cellular processes, including aspects of disease progression. In this work, we encapsulate and culture in three dimensions different cancer cell lines in a synthetic extracellular matrix (ECM), using mild and efficient chemistry. Specifically, harnessing the nucleophilic addition of thiols to activated alkynes, we have created hydrogel-based materials with multifunctional poly(ethylene glycol) (PEG) and select biomimetic peptides. These materials have definable, controlled mechanical properties ( G'  = 4–10 kPa) and enable facile incorporation of pendant peptides for cell adhesion, relevant for mimicking soft tissues, where polymer architecture allows tuning of matrix degradation. These matrices rapidly formed in the presence of sensitive breast cancer cells (MCF-7) for successful encapsulation with high cell viability, greatly improved relative to that observed with the more widely used radically-initiated thiol-ene crosslinking chemistry. Furthermore, controlled matrix degradation by both bulk and local mechanisms, ester hydrolysis of the polymer network and cell-driven enzymatic hydrolysis of cell-degradable peptide, allowed cell proliferation and the formation of cell clusters within these thiol-yne hydrogels. These studies demonstrate the importance of chemistry in ECM mimics and the potential thiol-yne chemistry has as a crosslinking reaction for the encapsulation and culture of cells, including those sensitive to radical crosslinking pathways. Graphical abstract: